Psychology for AS-level - Cardwell, Mike.; Clark, Liz, 1952-; Meldrum, Claire (London : Collins, 2003)
This text has been updated to reflect the revised AQA(A) specifications. Written by subject specialists and edited by experienced examiners and teachers, it guides the reader through every aspect of the course, providing clear and accessible information as well as tips and advice from a leading examiner.
Previous ed.: 2000.
Includes bibliographical references (p. 273-276) and index.
Keywords: Psychology; Psychology -- Examinations -- Study guides; Psychology